Ecological risk assessment and early warning of heavy metal cumulation in the soils near the Luanchuan molybdenum polymetallic mine concentration area, Henan Province, central China - Zhen-yu Chen; Yuan-yi Zhao; Dan-li Chen; Hai-tao Huang; Yu Zhao; Yu-jing Wu (China Geology)
The Luanchuan molybdenum polymetallic mine concentration area is rich in mineral resources and has a long history of mining. The environmental impact of long-term mining activities cannot be ignored. It is of great significance to study the ecological risk and the accumulation trends of heavy metals in the soil of mining areas for scientific prevention and control of heavy metal pollution. Taking the Taowanbeigou River Basin in the mine concentration area as the research object, the ecological pollution risk and cumulative effect of heavy metals in the soil of the basin were studied by using the comprehensive pollution index method, potential ecological risk assessment method and geoaccumulation index method. On this basis, the cumulative exceeding years of specific heavy metals were predicted by using the early warning model. The comprehensive potential ecological risk of heavy metals in the soil near the Luanchuan mine concentration area is moderate, and the single element Cd is the main ecological risk factor, with a contribution rate of 53.6%. The overall cumulative degrees of Cu and Pb in the soil are “none-moderate”, Zn and Cd are moderate, Mo has reached an extremely strong cumulative level, Hg, As and Cr risks are not obvious, and the overall cumulative risks order is Mo>Cd>Zn>Cu>Pb>Hg. According to the current accumulation rate and taking the risk screening values for soil contamination of agricultural land as the reference standard, the locations over standard rates of Cu, Zn and Cd will exceed 78% in 90 years, and the over standard rate of Pb will reach approximately 57% in 200 years. The cumulative exceeding standard periods of As, Cr and Hg are generally long, which basically indicates that these elements do not pose a significant potential threat to the ecological environment. Mining activities will accelerate the accumulation of heavy metals in soil. With the continuous development of mining activities, the potential pollution risk of heavy metals in the soil of mining areas will also increase.©2023 China Geology Editorial Office.